Associated Risks in Surgery for Juvenile Nasopharyngeal Angiofibroma: Evaluation of the Endoscopic Technique Versus the Open Technique (Revista de Medicina Clinica, 2022)
Introduction: Juvenile nasopharyngeal angiofibroma represents less than 0.05% of head and neck tumors. It originates from the region of the sphenopalatine foramen, can extend into the nasal cavity, paranasal sinuses, pterygopalatine fossa, and the infra-temporal fossa, and may invade base of the skull. The objetive was to evaluate the risk factors associated with the two main surgical techniques for resection of AJNF in a series of cases. Patients and methods: Retrospective, cross-sectional analytical study of a series of cases from 2014 to 2018, demographic variables were taken, as well as clinical and surgical data. Descriptive statistics and analysis were performed with Fisher's exact test and it was considered significant if p1 yr and 45.8%
Keywords: Angiofibroma juvenile; Nasopharyngeal; Risks; Surgery